Gamma-Ray Emission Produced by r-process Elements from Neutron Star Mergers - Chen, Meng-Hua; Li, Li-Xin; Lin, Da-Bin; Liang, En-Wei (The Astrophysical journal, 2021)
The observation of a radioactively powered kilonova AT 2017gfo associated with the gravitational wave event GW170817 from a binary neutron star merger proves that these events are ideal sites for the production of heavy r -process elements. The gamma-ray photons produced by the radioactive decay of heavy elements are unique probes for the detailed nuclide compositions. Based on the detailed r -process nucleosynthesis calculations and considering radiative transport calculations for the gamma rays in different shells, we study the gamma-ray emission in a merger ejecta on a timescale of a few days. It is found that the total gamma-ray energy generation rate evolution is roughly depicted as E ̇ ∝ t − 1.3 . For the dynamical ejecta with a low electron fraction ( Y e ≲ 0.20), the dominant contributors of gamma-ray energy are the nuclides around the second r -process peak ( A ∼ 130) and the decay chain of 132 Te ( t 1/2 = 3.21 days) → 132 I ( t 1/2 = 0.10 days) → 132 Xe produces gamma-ray lines at 228, 668, and 773 keV. For the case of a wind ejecta with Y e ≳ 0.30, the dominant contributors of gamma-ray energy are the nuclides around the first r -process peak ( A ∼ 80) and the decay chain of 72 Zn ( t 1/2 = 1.93 days) → 72 Ga ( t 1/2 = 0.59 days) → 72 Ge produces gamma-ray lines at 145, 834, 2202, and 2508 keV. The peak fluxes of these lines are 10 −9 ∼ 10 −7 ph cm −2 s −1 , which are marginally detectable with the next-generation MeV gamma-ray detector ETCC if the source is at a distance of 40 Mpc.